Tradisionalisme Dalam Arsitektur Kolonial Belanda Di Kota Malang - Joko Triwinarto Santoso; Noviani Suryasari; Antariksa Antariksa (RUAS (Review of Urbanism and Architectural Studies), 2013)
People are not able to break away from the past that gave birth to (system) values and thoughts derived continuously without or with very few changes. This kind of understanding is called as traditionalism. Traditionalism is also in the architecture as a product of human culture. Malang as the town grew rapidly during the Dutch colonial period, saved some buildings from that era. Architecture of these buildings is certainly a result of the design which is based on a wide range of ideologies, one of which is tradisionalism. This study that seeks to identify the presence of traditionalism in the Dutch colonial architecture using descriptive methods (graphics), with data obtained by purposive sampling technique. The results obtained indicate that there is influence of traditionalism in the Dutch colonial architecture embodied in the two architectural elements, namely the roof and openings.Keywords: tradisionalism, Dutch colonial architecture, Malang